2021
DOI: 10.3389/fpsyt.2021.730415
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Age-Group Latent Mean Differences in Maladaptive Identity in Adolescence

Abstract: Little is known about the differences between age groups in maladaptive personality function as denoted in Criterion A of the Alternative Model for Personality Disorder (AMPD) in the DSM-5, which is the entry criterion for diagnosing personality disorder in the upcoming ICD-11. The current study aimed to address this gap by evaluating latent mean age group differences in maladaptive identity, which is one aspect that has been identified as an important feature of maladaptive, general personality function as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Previous evidence on maladaptive personality traits suggest that features of personality pathology emerge in early adolescence, reach their peak in middle adolescence, and then decrease as adolescents enter adulthood [50]. Similarly, recent research revealed the normative increase in maladaptive identity throughout adolescence, which was closely related to increases in borderline personality features, especially for older adolescents [51]. However, our data catches the wider scope of general severity in personality functioning rather than discrete personality features so it is possible that even though personality features might change, the general level of personality functioning follows a more complex pattern of change.…”
Section: Discussionmentioning
confidence: 91%
“…Previous evidence on maladaptive personality traits suggest that features of personality pathology emerge in early adolescence, reach their peak in middle adolescence, and then decrease as adolescents enter adulthood [50]. Similarly, recent research revealed the normative increase in maladaptive identity throughout adolescence, which was closely related to increases in borderline personality features, especially for older adolescents [51]. However, our data catches the wider scope of general severity in personality functioning rather than discrete personality features so it is possible that even though personality features might change, the general level of personality functioning follows a more complex pattern of change.…”
Section: Discussionmentioning
confidence: 91%
“…Over the last decade, many studies have employed the BFSFC-SF to screen personality features of adolescents ( 39 43 ). For example, Biberdzic et al used the BFSFC-SF to assess adolescents' core domains of functioning; Barkauskiene et al used BFSFC-SF to screen adolescent borderline personality features to provided information for the established DSM-V. Hendriks et al used the BFSFC-SF to explore the psychopathological correlates of implicit and explicit shame and guilt; Sharp et al used the BFSFC-SF to investigate maladaptive identity formation in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Against this background, we expected a significant association between intimacy (perceived parental closeness) and identity diffusion so that greater distance in perceived parental closeness (i.e., less feelings of parental closeness) would be associated with higher levels of identity diffusion. We also expected identity diffusion to relate to borderline features-a finding which has already been established in adolescence (53)(54)(55).…”
Section: Introductionmentioning
confidence: 96%